2013
DOI: 10.1186/1471-2180-13-255
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide (LPS)-induced autophagy is involved in the restriction of Escherichia coliin peritoneal mesothelial cells

Abstract: BackgroundHost cell autophagy is implicated in the control of intracellular pathogen. Escherichia coli (E.coli) is the most common organism caused single-germ enterobacterial peritonitis during peritoneal dialysis. In this study, we investigated autophagy of peritoneal mesothelial cells and its role in defense against E.coli.ResultsAutophagy in human peritoneal mesothelial cell line (HMrSV5) was induced by lipopolysaccharide (LPS) in a dose-dependent and time-dependent way, which was demonstrated by increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 26 publications
(42 reference statements)
3
24
0
Order By: Relevance
“…The role of TLR4 is somewhat controversial. Colmont et al demonstrated that TLR4 was not expressed in primary cultured human PMCs and LPS also did not induce any inflammatory molecules tested [11], whereas it was strongly expressed in a cell line (HMrSV5 cells) and LPSinduced autophagy was dependent on TLR4 in the cells [16,17]. Bacterial and viral peritonitis can occur in patients with intestinal perforation or undergoing continuous ambulatory peritoneal dialysis (CAPD) [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The role of TLR4 is somewhat controversial. Colmont et al demonstrated that TLR4 was not expressed in primary cultured human PMCs and LPS also did not induce any inflammatory molecules tested [11], whereas it was strongly expressed in a cell line (HMrSV5 cells) and LPSinduced autophagy was dependent on TLR4 in the cells [16,17]. Bacterial and viral peritonitis can occur in patients with intestinal perforation or undergoing continuous ambulatory peritoneal dialysis (CAPD) [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…LPS-induced autophagy is involved in the restriction of Escherichia coli in peritoneal mesothelial cells [26]. To determine whether LPS induces autophagy, MH-S cells were transfected with RFP-LC3 plasmids or GFP-LC3 plasmid.…”
Section: Resultsmentioning
confidence: 99%
“…Such large autophagosomal structures were not seen upon serum starvation of the Saos‐2 cells suggesting signaling specificity in assembly of these structures with LPS 1690 . Similarly, very large autophagic structures, termed mega‐phagosomes, have been observed with coxsackievirus B3 infection (Kemball et al ., ), as well as E. coli LPS‐induced autophagy and subsequent infection (Wang et al ., ). In the case of coxsackievirus B3 infection, these large vacuoles are non‐degradative so providing the virus with a replicative niche.…”
Section: Discussionmentioning
confidence: 99%